Da invisibilização à evidenciação dos saberes ambientais da comunidade do povoado Ribeira no entorno do Parque Nacional Serra de Itabaiana - Nascimento, Luanne Michella Bispo (2014)
This work was motivated by the lack of studies in the Sierra National Park Itabaiana that clings to the study of local knowledge of local residents in your surrounding. Currently, we observe the existence of an experienced gridlock on one side by the creation of Conservation Units (CU s) that imposes legal use of natural resources constraints and on the other, the reality of the settlements characterized by economic dependence on its residents to natural resources and unsustainable economic and cultural activities. Environmental laws by defining the use of that space can cause, directly or indirectly, environmental conflicts. In the conservation process, knowledge about the use and sustainable management of natural resources, their ideological formations, cultural practices and traditional techniques, constituting the environmental knowledge of a community, can be considered. For this, one must understand that the environmental issue is inherently conflictual because resource use is subject to conflicts between different designs, meanings and purposes. This research will highlight the importance of local knowledge, as many scientists argue that the presence of populations within parks can contribute significantly to the success of these conservation areas. The overall goal of this research is to analyze the knowledge, local knowledge, forms of ownership of the community in relation to the environment, correlating them with the socioeconomic context in Ribeira populated. From these surveys, the paper intends to talk about the complex web of inter-relationships mentioned above, to thereby form the environmental knowledge. The problem refers to the process of increasing invisibilization experienced by communities surrounding protected areas as a result of the implementation, management and maintenance of CU s, which only promote conservation of environmental structures, relegating to the background social diversity . Therefore, the methodology adopted was based on ethno-ecological studies, conducting field work, which were developed by techniques of oral history, especially the history of life. During the field research quantitative and qualitative interviews were conducted. The transcript, systematization and analysis of data followed the technique of discourse analysis. In addition, we constructed a comparative table of cognition, in which the locations are compared and scientific knowledge. Through research it is concluded that the increased knowledge about the plants and animals as well as the retention of them are related to the utility aspect that offer residents and not the ecological value of each. Such knowledge of scientific approach, others do not. There was a process of community invisibilization both the implementation process PARNASI as in management. In an attempt to alleviate the problems of managing PARNASI could promote environmental education to try greening knowledge and understanding of local communities. From the discussions, we point to the need to overcome paradigmatic, seeking an environmental paradigm that stick to the existing socio-bio-diversity conservation units. Thus, it is expected that to be ecologically suited environmental knowledge can promote a process of desinvisibilization local communities, contributing positively to the conservation process in UC´s.